Alberdi, Inés y Pilar Escario, Los hombres jóvenes y la paternidad, Bilbao, Fundación BBVA, 2007 - Rojas, Olga Lorena (El Colegio de México A.C., 2009)
Alberdi, Inés y Pilar Escario. (2007). Los hombres jóvenes y la paternidad, Bilbao, Fundación BBVA.